2000
DOI: 10.1097/00042560-200012152-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effective Detection of HIV

Abstract: Summary: Biomedical advances, new HIV testing technologies, and policy shifts in the last 15 years have created substantial new challenges and opportunities for service providers, policy makers, and researchers regarding broad scale identification of HIVseropositive persons. Effective HIV testing will be achieved when we: (1) increase the number of high-risk persons tested; (2) decrease the time from HIV infection to detection; (3) increase testing acceptability; (4) increase the proportion of individuals test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 106 publications
0
17
0
3
Order By: Relevance
“…HIV testing may help people who are exposed to the risk of HIV infection know their HIV serostatus in order to have early treatment and prevent transmission to others [1]; HIV testing provides an effective means of secondary prevention, especially for those tested positive [2]. Literature documents the dilemma between high rates of acceptance of testing and low rates of actual testing (including not returning for results) [3].…”
Section: Introductionmentioning
confidence: 99%
“…HIV testing may help people who are exposed to the risk of HIV infection know their HIV serostatus in order to have early treatment and prevent transmission to others [1]; HIV testing provides an effective means of secondary prevention, especially for those tested positive [2]. Literature documents the dilemma between high rates of acceptance of testing and low rates of actual testing (including not returning for results) [3].…”
Section: Introductionmentioning
confidence: 99%
“…They have good user and provider acceptability, and safety. A potential advantage could be that, as more infected individuals learn their status and reduce risk behaviours, HIV transmission will decrease (1,2,12). In 1995, 25% of persons testing HIV positive at American publicly funded clinics did not return for their results (22).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of occupational safety, there is much less risk of health care worker exposure with finger prick than with venipuncture (24). The need to return for results has previously been identified as one barrier to acceptance of testing (2,23). It has since been shown that sexually transmitted disease and HIV testing clinic clients preferred the convenience of rapid to standard testing (14).…”
Section: Point-of-care Hiv Tests: Test Characteristics Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers for attending medical care and receiving antiretroviral therapy include lower socioeconomic status, competing subsistence needs, injecting drug abuse and affiliation with a minority group [19][20][21]. To diminish the number of undiagnosed HIV infections, primary care providers should mainstream HIV testing as routine clinical care, especially in high-risk groups [22].…”
Section: Discussionmentioning
confidence: 99%